Carbon Stock of Mangrove Vegetation Derived from Aboveground and Belowground Biomass in Tulehu Waters, Central Maluku - Natsir, Nur Alim; Mulyawati, Nina Y.; AF, Asyik Nur Allifah; Jamdin, Zamrin; Arifin, Selti; Kilbaren, Rukaya (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The role of mangroves in mitigating climate change is realized through their carbon storage capacity, but deforestation carried out for the expansion of the Tulehu pier threatens the existence of these carbon reserves. This study aims to estimate mangrove vegetation carbon stocks based on aboveground biomass and belowground biomass in Tulehu Waters, Central Maluku. Sampling was conducted using purposive sampling using a non-destructive allometric model on a 10 x 10 m plot. Aboveground and belowground biomass were calculated and then converted into mangrove carbon stocks. Data evaluation was carried out by measuring mangrove biomass and carbon stocks in the Tulehu Waters. Research findings show that the average carbon reserves of mangrove vegetation are the highest on the surface were found at station II (17,571 tC/ha), and underground were found at station (15,222 tC/ha). These findings confirm that mangrove vegetation in Tulehu Waters has significant potential as a carbon sink and support conservation strategies and sustainable coastal management.